Are the functions of non-suicidal self-injury associated with its persistence and suicide risk in university students? Insights from a network analysis - Szewczuk-Bogusławska, Monika; Kowalski, Krzysztof; Bogudzińska, Bogna; Misiak, Błażej (Frontiers in Psychiatry, 2024)
BackgroundTo date, a number of intra- and interpersonal functions of non-suicidal self-injury (NSSI) have been identified. Yet, their association with persistence of NSSI and suicide risk remains unknown. The study aimed to investigate which functions of NSSI are associated with its persistence and suicide risk in university students using a network analysis.MethodsAltogether, 830 university students reporting a lifetime history of NSSI were enrolled. The persistence of NSSI was defined as its presence over preceding 12 months.ResultsPersistent NSSI was directly connected to the nodes representing two functions of NSSI: affect regulation and self-punishment. Suicide risk was directly connected to the anti-suicide function of NSSI. The shortest pathway from persistent NSSI to suicide risk led through depressive symptoms. Other likely pathways (three mediating nodes) led through the functions of NSSI (affect regulation or self-punishment, anti-dissociation, and anti-suicide). Depressive symptoms had the highest centrality. However, it did not differ significantly compared to some functions of NSSI (marking distress, anti-dissociation, toughness, and affect regulation).DiscussionIn university students, persistent NSSI might be directly associated with its functions related to affect regulation and self-punishment, while suicide risk might be directly associated with the anti-suicide function. The observations posit a role of intrapersonal functions in shaping the outcomes of NSSI. Depressive symptoms and some NSSI functions might be the most promising targets for interventions in this population.